2020
DOI: 10.1177/0020764019894609
|View full text |Cite
|
Sign up to set email alerts
|

Turkish newspaper articles mentioning people with mental illness: A retrospective study

Abstract: Background: Because a great majority of the public knows about mental disorders primarily through printed or visual media, the attitudes exhibited in mass media might be predictive in stigmatizing individuals with mental disorders. Aim: The aim of this study was to retrospectively assess the articles in Turkish newspapers that mention individuals with mental disorders. Method: This study was designed to retrospectively investigate and analyze newspaper content in Turkey; the newspapers’ circulation information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
1
7
1
Order By: Relevance
“…The results of the present study are supported by those from research over the past decade, which has indicated that negative attitudes towards individuals with mental disorders among nursing students in Turkey have not changed 20,29 . Stigmatization towards individuals with mental disorders is explained by a complex structure, which includes many factors, such as the historical background of the society, the interaction of the society with patients, and the media 30 . Personal prejudices may act as barriers and may discourage students from evaluating sexual health 7 .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The results of the present study are supported by those from research over the past decade, which has indicated that negative attitudes towards individuals with mental disorders among nursing students in Turkey have not changed 20,29 . Stigmatization towards individuals with mental disorders is explained by a complex structure, which includes many factors, such as the historical background of the society, the interaction of the society with patients, and the media 30 . Personal prejudices may act as barriers and may discourage students from evaluating sexual health 7 .…”
Section: Discussionsupporting
confidence: 83%
“…20,29 Stigmatization towards individuals with mental disorders is explained by a complex structure, which includes many factors, such as the historical background of the society, the interaction of the society with patients, and the media. 30 Personal prejudices may act as barriers and may discourage students from evaluating sexual health. 7 Stigmatization must be eliminated in nursing students, who are future health professionals, in the education process.…”
Section: Discussionmentioning
confidence: 99%
“…33 While stigmatization usually presents as combining mental disorder and violence, crime, unpredictability, and dangerousness, sexual aggression is also a common theme addressed in general society and in the media. 34,35 Stigmatizing attitudes toward people with mental disorders should be assessed multidimensionally, along with societal stereotypes (past to present), the individual experiences of society members and peer interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies report no differences in stigmatization between health professionals and the general public, while others argue that health professionals have even more negative attitudes than the general population 33 . While stigmatization usually presents as combining mental disorder and violence, crime, unpredictability, and dangerousness, sexual aggression is also a common theme addressed in general society and in the media 34,35 . Stigmatizing attitudes toward people with mental disorders should be assessed multidimensionally, along with societal stereotypes (past to present), the individual experiences of society members and peer interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies show how the way in which information about people with MD is delivered encourages positive attitudes or, on the contrary, contributes to the formation of prejudices (Alyousef et al, 2019; Corrigan et al, 2013; Ross et al, 2019). The media often present distorted and negative images of MDs, associating them with aggressiveness, lack of control and criminality; people with MD are seen as a danger to others and to themselves (Aci et al, 2020; Bowen et al, 2019; Klin & Lemish, 2008; Nawková et al, 2012; Subramanian, 2018). Further research indicates that these lead to public perceptions that people with MD are violent and characterised by outbursts of anger, childlike behaviours and severe symptoms (Quintero Johnson & Riles, 2016; Reavley et al, 2016).…”
Section: Introductionmentioning
confidence: 99%